2017
DOI: 10.3906/biy-1705-50
|View full text |Cite
|
Sign up to set email alerts
|

Optimizations needed for lateral flow assay for rapid detection of pathogenic E. coli

Abstract: IntroductionMany strains of Escherichia coli bacteria live in the gastrointestinal tracts of humans and animals. E. coli O157 was reported as a food pathogen after the hemorrhagic colitis outbreak of 1982 (Riley et al., 1983). O157:H7 is one of the most important E. coli strains transmitted from cattle/ animals to humans (Dorn and Angrick, 1991;Altekruse et al., 1997;Slutsker et al., 1998), either by contact, eating contaminated foods, drinking contaminated water, or passing from one person to another directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Reinholt et al [17] showed that an electrospun polylactic acid-polyethylene glycol (PLA-PEG) mat without further advancements is comparable in use as a lateral flow assay to a classic nitrocellulose membrane (Figure 1). They demonstrated its use as a matrix in an antibody-based Escherichia coli immunoassay, achieving a limit of detection of 3.8 × 10 6 CFU/mL, which is comparable to those seen in the literature for nitrocellulose membranes [18,19].…”
Section: Randomly-aligned Nanowiresmentioning
confidence: 62%
“…Reinholt et al [17] showed that an electrospun polylactic acid-polyethylene glycol (PLA-PEG) mat without further advancements is comparable in use as a lateral flow assay to a classic nitrocellulose membrane (Figure 1). They demonstrated its use as a matrix in an antibody-based Escherichia coli immunoassay, achieving a limit of detection of 3.8 × 10 6 CFU/mL, which is comparable to those seen in the literature for nitrocellulose membranes [18,19].…”
Section: Randomly-aligned Nanowiresmentioning
confidence: 62%
“…If the test strip works correctly and it is positive, both the test and control lines are seen as red. If no colored capture lines or only a red color at the test line appears, the strip is invalid, and the test should be repeated [21,23,24] ( Figure 2).…”
Section: Lateral Flow Assaymentioning
confidence: 99%
“…The disadvantage of dipping the strip into bacterial media directly is that flow can be retarded on conjugate pad because of the media components. Thus, using the suitable running buffer, simple phosphate buffer saline (PBS), may enable conjugate to flow through the strip test, efficiently [21,27]. Third is the immobilization of capture reagents.…”
Section: Lateral Flow Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, an AuNPs‐based LFIA is sensitive, simple and rapid assay for E. coli O157:H7 detection because it can be visually analyzed, does not require the skilled personnel and the availability of cost effective and large scale LFIA strips production ability (Çam, 2019). However, AuNPs‐based LFIA still have a lot of restrictions with respect to target agents of detection and assay conditions of LFIA (Borse et al, 2020; Çam & Öktem, 2017; Peruski & Peruski, 2003). In spite of the widespread use of AuNPs as a label in LFIA, there are still many additional molecules and methods used on LFIA development.…”
Section: Techniques Of Lateral Flow Immunoassaymentioning
confidence: 99%